2014
DOI: 10.1016/j.jmb.2014.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Architecture of Photoreceptor Phosphodiesterase Elucidated by Chemical Cross-Linking and Integrative Modeling

Abstract: Photoreceptor phosphodiesterase (PDE6) is the central effector enzyme in visual excitation pathway in rod and cone photoreceptors. Its tight regulation is essential for the speed, sensitivity, recovery and adaptation of visual detection. Although major steps in the PDE6 activation/deactivation pathway have been identified, mechanistic understanding of PDE6 regulation is limited by the lack of knowledge about the molecular organization of the PDE6 holoenzyme (αβγγ). Here, we characterize the PDE6 holoenzyme by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 59 publications
9
52
0
Order By: Relevance
“…The results reveal added mass of the correct size and shape for an Fab fragment at the "top" of the structure, i.e. near the GAFa domain, for the N-terminal epitope tag, and near the catalytic domain for the C-terminal tag, consistent with previous cross-linking results (20,27,64). The distance between the two HA-Fab binding sites is ϳ90 Å (Fig.…”
Section: Low Resolution Structure Of Pde6 In Vitreoussupporting
confidence: 90%
See 3 more Smart Citations
“…The results reveal added mass of the correct size and shape for an Fab fragment at the "top" of the structure, i.e. near the GAFa domain, for the N-terminal epitope tag, and near the catalytic domain for the C-terminal tag, consistent with previous cross-linking results (20,27,64). The distance between the two HA-Fab binding sites is ϳ90 Å (Fig.…”
Section: Low Resolution Structure Of Pde6 In Vitreoussupporting
confidence: 90%
“…6. These results are contrary to previously published PDE6 GAF domain orientations based on a low resolution map (14), but in good agreement with a recently published model of PDE6 (64). The location of the non-catalytic cGMP binding site, inferred from the fitting of the cone PDE6C GAFa/cGMP crystal structure (9) (PDB ID 3DBA), is shown in Fig.…”
Section: Low Resolution Structure Of Pde6 In Vitreoussupporting
confidence: 71%
See 2 more Smart Citations
“…For example, it was demonstrated that a more integrated view of the subunit arrangement of an intact protein complex can be obtained by examining a sample with XL-MS, native MS, and ion-mobility spectrometry coupled to MS so that the complementary structural MS methods provide additional and orthogonal restraints compared with using XL-MS alone [48]. Advanced computational pipelines can support integration of the different types of data from crosslinking and from other sources -such as complementary experimental or computational methods -to facilitate the unbiased use of crosslinking and other restraints to generate reliable models for protein complexes [49][50][51][52]. This led to the generation of a generic hybrid approach for the accurate modeling of large protein assemblies, where XL-MS together with partial crystal structures of subunits were successfully integrated with modeling.…”
mentioning
confidence: 99%